Phenotypic Heterogeneity Affects Stenotrophomonas maltophilia K279a Colony Morphotypes and β-Lactamase Expression - Abda, Ebrahim M.; Krysciak, Dagmar; Krohn-Molt, Ines; Mamat, Uwe; Schmeisser, Christel; Förstner, Konrad U.; Schaible, Ulrich E.; Kohl, Thomas A.; Nieman, Stefan; Streit, Wolfgang R. (Frontiers in Microbiology, 2015)
Phenotypic heterogeneity on the cellular level in response to various stresses e.g. antibiotic treatment has been reported for a number of bacteria. In a clonal population, cell-to-cell variation may result in phenotypic heterogeneity that is a mechanism to survive changing environments including antibiotic therapy. Stenotrophomonas maltophilia has been frequently isolated from cystic fibrosis patients, can cause numerous infections in other organs and tissues, and is difficult to treat due to antibiotic resistances. S. maltophilia K279a produces the L1 and L2 β-lactamases in response to β-lactam treatment. Here we report that the patient isolate S. maltophilia K279a diverges into cellular subpopulations with distinct but reversible morphotypes of small and big colonies when challenged with ampicillin. This observation is consistent with the formation of elongated chains of bacteria during exponential growth phase and the occurrence of mainly rod-shaped cells in liquid media. RNA-seq analysis of small versus big colonies revealed differential regulation of at least seven genes among the colony morphotypes. Among those, blaL1 and blaL2 were transcriptionally the most strongly upregulated genes. Promoter fusions of blaL1 and blaL2 genes indicated that expression of both genes is also subject to high levels of phenotypic heterogeneous expression on a single cell level. Additionally, the comE homologue was found to be differentially expressed in homogenously versus heterogeneously blaL2 expressing cells as identified by RNA-seq analysis. Overexpression of comE in S. maltophilia K279a reduced the level of cells that were in a blaL2-ON mode to 1 % or lower. Taken together, our data provide strong evidence that S. maltophilia K279a populations develop phenotypic heterogeneity in an ampicillin challenged model. This cellular variability is triggered by regulation networks including blaL1, blaL2 and comE.